2016
DOI: 10.1093/icvts/ivv367
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of computerized tomography scan for reducing complications following repeat sternotomy for cardiac surgery

Abstract: Cardiac reoperation carries additional risks compared with surgery in patients who are sternotomy-naïve. To identify if preoperative computerized tomography (CT) can reduce this risk, we performed a systematic review of the literature and meta-analysis. Literature search identified 178 studies of which 4 retrospective cohort studies incorporating 900 patients met inclusion criteria. There were no statistically significant differences in the risk of death, re-entry injury, renal failure or perfusion/ischaemic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…[3,4,7] Additionally, prior to resternotomy, NCCCT can delineate the anatomical relationship of mediastinal structures and their proximity to the posterior surface of the sternum, as well as identify previously placed coronary grafts that may be injured upon re-entry. [3,6,15] Patients with more atherosclerotic disease in the ascending aorta are signi cantly more likely to have a higher incidence of carotid artery disease. [12] Pre-operative CD evaluation can be used to identify signi cant atherosclerosis of the internal carotid artery, but is typically considered for high risk patients that are older than 80, have a carotid bruit, or have a history of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4,7] Additionally, prior to resternotomy, NCCCT can delineate the anatomical relationship of mediastinal structures and their proximity to the posterior surface of the sternum, as well as identify previously placed coronary grafts that may be injured upon re-entry. [3,6,15] Patients with more atherosclerotic disease in the ascending aorta are signi cantly more likely to have a higher incidence of carotid artery disease. [12] Pre-operative CD evaluation can be used to identify signi cant atherosclerosis of the internal carotid artery, but is typically considered for high risk patients that are older than 80, have a carotid bruit, or have a history of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative evaluation of the heart, great vessels and chest with imaging modalities such as echocardiography and chest radiography are performed routinely prior to cardiac surgery for selected patients [1][2][3]. However, as many cardiac surgical patients today are elderly, high risk with signi cant comorbidities, these imaging modalities may not fully provide an adequate preoperative assessment for surgical risk reduction and patient management [4][5][6]. Epi-aortic ultrasound has been proven to be effective for detecting calci ed plaques in the ascending aorta, however, is limited due to its intraoperative use, operator experience, time consumption [3,7] and has restricted use to the aorta.…”
Section: Introductionmentioning
confidence: 99%
“…Reentry of the thorax is a critical part of the operation, as dense adhesions of the right ventricle, the aortic graft or the innominate vein to the posterior sternal table renders these vital structures vulnerable to an increased risk of injury. A detailed preoperative CT scan of the thorax and the aorta should not only help plan the reentry into the thorax 17 but also provides clues for extrathoracic cannulation for CPB prior to reentry, if required. In such a way, the surgeon may avoid catastrophic reentry-related injuries.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis suggests that a history of previous cardiac surgery does not independently confer a significant incremental risk of operative mortality, but that patients with greater number of previous operations appear to be at higher risk." 1(p2) Several strategies for risk reduction in mortality and morbidity during resternotomy are described 8 : Polytetrafluoroethylene membrane, 3 preoperative chest computed tomography (CT), [9][10][11][12] use of an oscillating saw, 10,13 and peripheral cannulation. 10,11,14 The aim of this study was to describe the experience in reoperation of pediatric patients with congenital heart disease (CHD) in a center from a low-middle-income country and to determine the factors associated with operative mortality.…”
Section: Ctmentioning
confidence: 99%
“…1 Many centers use preoperative CT in a routine manner or in high-risk patients to develop a surgical plan in order to decrease the probability of cardiac injury during repeat sternotomy. [9][10][11][12] However, this type of preoperative evaluation increases the costs of each procedure and in a health system with limited resources such as ours, it represents an additional cost that is difficult to afford. In this study, we found that preoperative CT is not always necessary to achieve good results, using only a preoperative chest X-ray and angiogram to assess the relationship between cardiac structures and the sternum.…”
Section: Commentmentioning
confidence: 99%